2013
DOI: 10.1111/eos.12063
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tooth whitening with different calcium phosphate‐based formulations

Abstract: The aim of this in-vitro study was to evaluate the efficacy of tooth whitening using different calcium phosphate-based formulations. Teeth were treated with three different hydroxyapatite preparations at different concentrations and with two control preparations; each tooth was treated a total of three times. After application of the last material, hydrodynamic shear force was applied to mimic mechanical loading. After each treatment, tooth color was measured using a dental spectrophotometer, and the mean chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 15 publications
(20 reference statements)
2
54
0
3
Order By: Relevance
“…If a toothpaste has a very low abrasive value, a staining film accumulates on the restorative material surface . However, considering that the components described in the package leaflet may not explain the color changes that occur on the substrates, it is important to understand that it is the combined action of all the components that will either provide changes in the substrates, or not …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If a toothpaste has a very low abrasive value, a staining film accumulates on the restorative material surface . However, considering that the components described in the package leaflet may not explain the color changes that occur on the substrates, it is important to understand that it is the combined action of all the components that will either provide changes in the substrates, or not …”
Section: Discussionmentioning
confidence: 99%
“…7,11 However, considering that the components described in the package leaflet may not explain the color changes that occur on the substrates, it is important to understand that it is the combined action of all the components that will either provide changes in the substrates, or not. 24 Considering the surface roughness results, the studied hypothesis was partially accepted, because CLW toothpaste caused a higher change in surface roughness (ΔR a ) in Tetric when compared with toothbrushing with SDB (P < .0001) and CWN (P = .0044). For Z250 and Z350, CLW toothpaste resulted (P < .0001) in smoother surfaces when compared with the Tetric.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that dental bleaching alters the enamel chemically and have shown decreased calcium values in enamel [5][6]8 . In order to minimize such demineralization after contact with bleaching agents, some biomaterials such as fluoride, hydroxyapatite, calcium ions and amorphous calcium have been added to the composition of those whitening agents 9 . Beneficial effects of combining these substances with bleaching agents have been verified in previous studies 3, [9][10] , which concluded that such association may protect the enamel from demineralization and also may avoid hypersensitivity during the procedure.…”
Section: Introductionmentioning
confidence: 99%
“…In order to minimize such demineralization after contact with bleaching agents, some biomaterials such as fluoride, hydroxyapatite, calcium ions and amorphous calcium have been added to the composition of those whitening agents 9 . Beneficial effects of combining these substances with bleaching agents have been verified in previous studies 3, [9][10] , which concluded that such association may protect the enamel from demineralization and also may avoid hypersensitivity during the procedure. However, fluoride and calcium addition to the bleaching agents were not sufficient to increase the microhardness of enamel 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Mas, deve-se considerar que os componentes descritos na bula, individualmente, podem não explicar as alterações de cor ocorridas nos substratos. É importante compreender que a ação combinada de todos eles é que proporcionarão alterações nos substratos ou não (92).…”
Section: Discussionunclassified